PASAR SAYUR DI KAMPUNG SAYUR LANDASAN ULIN UTARA BANJARBARU - Mumtaaz, Dhiandra Kirana; Oktaviana, Anna (UNIVERSITAS LAMBUNG MANGKURAT, 2024)
This journal discusses the planning and design of the North Ulin Platform Vegetable Market with a Sustainable Architecture approach. The vegetable market is an important space for social interaction on an urban scale. The market acts as a means of distribution of agricultural goods and has a strategic role in the food security of a region. Kampung Sayur LAURA in Banjarbaru City, South Kalimantan, is a government effort to increase agricultural productivity and the local economy. This area is planned as a center for the production of quality agricultural products. The Municipal Government of Banjarbaru plans to establish a Vegetable Market in Kampung Sayur LAURA to facilitate the buying and selling of agricultural commodities. However, the existing vegetable market is still not optimal in trading farmer's commodities. In addition, vegetables are often delivered through collectors, which causes price increases. Therefore, proper planning and design is needed to build the LAURA Kampung Sayur Vegetable Market. Vegetable Market Kampung Sayur LAURA must be designed with characteristics that suit the needs of the vegetable market. In addition, infrastructure that supports the growth of the agricultural sector needs to be accommodated to meet the quality standards set by the Indonesian Ministry of Agriculture. Sustainable Architecture was chosen as the design approach for LAURA's Kampung Sayur Vegetable Market. This approach includes three pillars of design strategy, namely economic, social and environmental balance. By adopting this concept, it is hoped that the vegetable market can contribute in economic, ecological and social aspects.